A Model for the Development of A Chatter Bot/Chat Bot for Field of Public Health using the Example of Automated Online Breast Feeding Helper - Himanshi, H.L.N.; Karunathilake, I.M. (International Journal of Advanced Trends in Computer Science and Engineering, 2019)
The purpose of this paper is to provide a reference mode for the development of a chatter bot for field of Public Health using the example “Breast Feeding Helper”. This project a carried out using the AIML language and the platform” Pandorabot”. Use of Chat bot is new to the field for public health. The motivation behind this work is to make an initiative and demonstrate that it is feasible to develop a chatbot for the field of public health. This paper illustrates the steps and process of developing a chat bot for a topic in the field of public health. The steps and process described could be used as a model for further work.
Keywords: Artificial Intelligence; Chatterbot; Recognition; Pattern; Artificial Intelligence Markup Language (AIML)